Manual hyperinflation versus rib springing technique in mechanically ventilated patients with lung collapse - Manar Hussein Mohamed Dokhan; Ahmed Yassin Elsisi; Akram Abdelaziz Elsayed; Heba Ali Abdelghafar (Cairo : Manar Hussein Mohamed Dokhan, 2021)
Background: Lung collapse is a wide topic in ICU in mechanically ventilated patients. It is a typical cause of impaired gas exchange. Airway obstruction due to excess mucus is the most common etiological factor of lung collapse. Manual hyperinflation (MHI) and rib spring technique (RST) are common maneuvers in physical therapy in order to manage mechanically ventilated patients with collapsed lung aiming to re-inflate the lung, promote ventilation and mobilize secretions especially in smaller airways. Purpose: The main aim of this study was to detect the effect of manual hyperinflation versus rib springing technique in mechanically ventilated patients with lung collapse. Subjects: Forty adult injured patients with complete or partial lung collapse who were received mechanical ventilation and who were admitted to the intensive care unit participated in this study.Their ages ranged from 30 to 40 years. The participants were selected from National Bank Hospital-Specialized Medical Centers (intensive care unit), Cairo, Egypt from August 2019 to December 2020 and randomly distributed into two equal groups.Methods: Patients assigned in a random way into two equal groups (A and B). Group(A) (MHI group): twenty patients were received manual hyperinflation in addition to their traditional chest physical therapy program (nebulization / positioning / vibration / percussion / suctioning) for 30 minutes. Group (B) (RST group): twenty patients were received rib springing technique in addition to the same traditional treatment as group (A) also for 30 minutes. Each patient in both groups was assessed before treatment and reassessed after 4 successive sessions at a rate of one session per day regarding ABGs, chest x ray component of murray score and hemodynamic parameters. Results: Group (A) (MHI group) was significantly lower in PaCO2 when compared with that of group (B) (RST group) post treatment (p = 0. 02) and there was a significant increase in (PaO2, SaO2) of group (A) when compared with that of group (B) post treatment (p = 0. 02, p = 0.009) respectively. Murray score of group (A) post treatment was significantly lower than that of group (B) post treatment (p = 0.003)
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Cardiopulmonary and Geriatrics Disorder
Issued also as CD
Keywords: Lung collapse; MHI; RST